Freedom of expression and political culture in Nordic countries. Analysis of Prime Minister’s pressure on public service media in Finland - Chacińska, Maja Joanna (Political Preferences, 2017)
Nordic countries have been on top of transparency and freedom of expression indexes for years. Denmark topped Transparency International list for 2016 while Finland took first place on World Press Freedom Index 2017. However, it does not mean that Nordic politicians never try to interfere with media content. The purpose of this article is the analysis of pressure that politicians put on Nordic public service media. Serving as a showcase are the events that have recently taken place in Finland. Some elements of the Nordic political culture are also presented, as they can influence the society’s perception of political pressure on media. Key words: freedom of expression, Nordic countries, Finland, public service media